Plasma-melted nitrogen-bearing cast stainless - Sinha O.P.; Singh A.K.; Ramachandra C.; Gupta R.C. (My University, 2025)
Alloys of Fe-Cr-Ni and Fe-Cr-Mn were plasma arc-melted and chill cast in the form of ingots. Exposure of liquid melts to a nitrogen plasma for the purpose of adding nitrogen to the above alloys was used to dissolve varying amounts (up to 0.32 wt pct) of nitrogen. Carbon and sulfur were varied up to 0.5 and 0.056 wt pct, respectively. The alloys were evaluated for their mono- tonic behavior. It was observed that while strength and ductility parameters increased consid- erably with increasing nitrogen and carbon contents, both these parameters deteriorated with sulfur content. The analysis of the present results, along with the data from the literature, sug- gests that the strength parameters are predominantly chemistry dependent, particularly controlled by the nitrogen and carbon contents. The results also show that the alloys produced by this relatively new technique, plasma arc-melting, are comparable to those produced by other stan- dard techniques. © 1992 The Minerals, Metals & Materials Society - ASM Materials - The Materials Information Society.